EXTREME HAWKING RADIATION - Good, Michael R.R. (arxiv, 2020)
Modeling the collapse of an extreme Reissner-Nordstr¨om (ERN) black hole by solving the corre sponding moving mirror model for the trajectory that asymptotically approaches uniform accelera tion, we obtain the non-zero beta coefficients for all times. Finite energy is emitted, the radiation spectra is non-thermal (non-steady / not Planck), soft particles characterize the evaporation, and particle production at ultra-late times is damped. Entanglement entropy diverges with no Page curve turn-over, demonstrating non-thermal information loss. The radiation obeys time-reversal symmetry
Keywords: Type of access: Open Access; radiation; extreme Reissner-Nordstr¨om